Bank Consolidation and Performance : The Argentine Experience. (IMF Working Papers; Working Paper ;, 2004)
We examine a large panel of more than 100 banks from Argentina to study the effects of bank consolidation on performance between December 1995 and December 2000, a period of heavy bank consolidation and relative calm. Overall, we find a positive and significant effect of bank consolidation on bank performance. Bank returns increase with consolidation, and insolvency risk is reduced. Additionally, the study suggests that mergers and privatizations have a beneficial effect on bank returns. The effects of a bank acquisition on return on equity is, however, negative. Acquisitions do not seem to have any effect on risk-adjusted returns. The study also finds that a bank's insolvency risk is reduced significantly through mergers and privatization and is unrelated to bank acquisitions.